2020
DOI: 10.1002/cam4.2974
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the radiologic features of pneumonitis induced by anti‐PD‐1 therapy

Abstract: Background: Interstitial lung disease (ILD) induced by anti-programmed-cell death-1 (PD-1) and anti-PD-ligand 1 (PD-L1) is potentially life-threatening and is a common reason of the discontinuation of therapy. In contrast, an enhancement in antitumor effects was reported in patients who developed immune-related adverse events, including ILD. Although recent evidence suggests that radiologic patterns of ILD may reflect the severity of ILD and the antitumor immune responses to anti-PD-1/PD-L1 therapies, the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…The dispersion of our data may be due to the different patterns of interstitial lung toxicity observed in our relatively small cohort. The main radiological patterns were OP, HP-like parenchymal features and GGO, in line with previous data [ 8 , 27 , 28 ]; however, other radiological interstitial features were observed in these patients, including NSIP and UIP patterns. In our study, fibrotic ILD developed in a small percentage of patients, with a longer, albeit not significant, latency with respect to GGO and HP-like parenchymal features.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The dispersion of our data may be due to the different patterns of interstitial lung toxicity observed in our relatively small cohort. The main radiological patterns were OP, HP-like parenchymal features and GGO, in line with previous data [ 8 , 27 , 28 ]; however, other radiological interstitial features were observed in these patients, including NSIP and UIP patterns. In our study, fibrotic ILD developed in a small percentage of patients, with a longer, albeit not significant, latency with respect to GGO and HP-like parenchymal features.…”
Section: Discussionsupporting
confidence: 91%
“…Concerning the prognostic significance of different CT patterns, to our knowledge, only a paper by Watanabe et al [ 28 ] reported a direct comparison, demonstrating that patients developing GGO were affected by a worse prognosis and life expectancy than in those with OP. Our data seem to be in line with these observations, as the majority of patients who died early showed chest HRCT evidence of the GGO pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Specific findings on chest CT include traction bronchiectasis, consolidation, reticular opacities, ground glass opacities (GGOs), centrilobular nodularity, and honeycombing, of which GGOs are present in the majority of patients ( 66 ). In addition, GGO was indicated as a significant predictor of worse overall survival ( 67 ). Clinically, the situation will be more complicated, and mixed patterns may be observed.…”
Section: Occurrence Of Cip During Pd-1/pd-l1 Blockadementioning
confidence: 99%
“…In addition, they also observed increased numbers of central memory T cells and decreased expression of CTLA-4 and PD-1 in regulatory T cells (Tregs). Enriched IFNg + IL-17-CD8 + T and CXCR3 + CCR6 + Th17/Th1 cells were observed in the BALF of CIP compared with infection pneumonia in acute myeloid leukemia and myelodysplastic syndrome ( 67 ).…”
Section: Occurrence Of Cip During Pd-1/pd-l1 Blockadementioning
confidence: 99%
“…The decision of whether to continue or discontinue ICIs after the occurrence of irAEs is generally based on the type of irAE and its severity (7). We previously reported that ICI-related interstitial lung disease (ILD), whose appearance was ground-glass opacities (GGOs), was a significant predictor of poor survival outcomes (8). However, recent evidence has demonstrated that the occurrence of irAEs is associated with better survival outcomes in patients with NSCLC (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%